Der Text und seine Kultur(en) - Kablitz, Andreas; Markschies, Christoph Johannes; Strohschneider, Peter (Text und Textlichkeit, 2023)
This volume examines the phenomenon of text from a cross-cultural perspective in order to go beyond the often eurocentrically reductive interpretation of cultural practices outside of Europe and to gain new insights into the genuine achievements of language and text. It therefore expands interculturally upon the workgroup's research questions, which have been discussed in previous publications
Keywords: Konferenzschrift -- 2019 -- Köln; Kultur; Schriftlichkeit; Text